Deliberative democracy in local governance: the impact of institutional design on legitimacy. Issue 2 (4th March 2017) - Gundelach, Birte; Buser, Patricia; Kübler, Daniel
ABSTRACT: Deliberative democracy is expected to increase legitimacy and effectiveness of democratic governance. In recent years, a growing body of research has reported on different instances of participatory innovations across the globe. Nevertheless, quantitative evidence on the determinants of legitimate and effective deliberative procedures is still scarce. Examining parents' participation in school governance in Switzerland, this article explores the effect of the design of deliberative institutions on perceptions of legitimacy and effectiveness. Based on an original survey of 312 parent councils of public primary schools in Switzerland, the results of our analysis corroborate theoretical expectations about the impact of institutional design on legitimacy and effectiveness of deliberative procedures: More authority granted to parent councils clearly enhances the output-legitimacy of these bodies.